Intensive γ-ray light sources based on oriented single crystals - Gennady B. Sushko; Andrei V. Korol; Andrey V. Solov’yov (Physical Review Accelerators and Beams)
The feasibility of gamma-ray light sources based on the channeling phenomenon of ultrarelativistic electrons and positrons in oriented single crystals is demonstrated using rigorous numerical modeling. Case studies are presented for 10 GeV and sub-GeV e^{-}/e^{+} beams incident on 10^{-1}-10^{0}  mm thick diamond and silicon crystals. It is shown that for moderate values of the beam average current (≲10  μA), the average photon flux in the energy range of 10^{0}–10^{2}  MeV emitted within the 10^{1}–10^{3}  μrad cone and 1% bandwidth can be on the level of 10^{10}  photon/s for electrons and 10^{10}–10^{12}  photon/s for positrons. These values are higher than the fluxes available at modern laser-Compton gamma-ray light sources.